The golog programming language and agency - Gómez, Sergio Alejandro (2003)
In this paper, we present our initial experiences modeling agency in the situation calculus and the Golog programming language. We describe the problems we have faced and discuss some research issues that remain to be addressed in the future. As an application of this research line, we propose an axiomatization of the robot Charles and the Fantastic City in the situation calculus as well as a controller written in Golog.